METHOD DEVELOPMENT OF SONICATION TECHNIQUE EXTRACTION FOR DETERMINATION OF CARBOFURAN PESTICIDE IN SPIKE SOIL SAMPLE BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Yusiasih, Retno; Pitoi, Mariska M; Ariyani, Miranti (LIPI Press, 2018)
A method for determination of carbofuran pesticides residue utilizing extraction by sonication has been developed for spike soil sample collected from horticulture farms in Lembang, North Bandung Regency, Indonesia. The simple, reliable, and cost-effective method was performed without any clean up prior injection to HPLC-UV. The method was validated by evaluating its detection limit, linearity, repeatability, recovery, and matrix effect. The detection limit of the method is 0.50 mg/kg. The linearity of the method is very good (r=0.99677) for concentration range of 1.0 to 5.0 mg/kg. The repeatability of the method is acceptable (CV value of 2.56 %). The fortified recoveries are acceptable, ranging from 93.44 to 101.03%. Statistical analysis shows that the matrix effect is insignificant to the method. The application of the method is able to offer a minimization of waste, miniaturization of method, and increased the safety for the operator as required for Green Analytical Chemistry.